Depression in individuals with chronic obstructive pulmonary disease and their informal caregivers. (2nd September 2017) - Badr, Hoda; Federman, Alex D.; Wolf, Michael; Revenson, Tracey A.; Wisnivesky, Juan P.
ABSTRACT: Objective: Individuals with chronic obstructive pulmonary disease (COPD) and their caregivers are at high risk for developing depression. Depression can adversely affect the quality of life of patients and caregivers; however, studies in COPD have largely examined predictors of patient and caregiver depression in isolation. This dyadic study examined individual-level predictors of patient and caregiver depression in COPD (i.e. actor effects) as well as how dyad members effect each other's depression (i.e. partner effects). Methods: Survey data were collected from 89 patient–caregiver dyads that were enrolled in a multi-site cohort study. Results: Participants were predominantly women (61% of patients and 76% of caregivers) and racial/ethnic minorities (65% of patients and 63% of caregivers). Based on PHQ9 cutoffs, 30% of patients and 20% of caregivers had mild depression; 30% of patients and 8% of caregivers had moderate to severe depression. Multilevel models with the dyad as the unit of analysis showed that less frequent patient self-management, higher levels of caregiver burden, and being in poorer health were associated with higher levels of depression for both dyad members. Higher levels of depression in a partner were also associated with higher levels of depression for women, regardless of whether women were patients or caregivers. Conclusion: Findings suggest that similar factors predict patient and caregiver depression in COPD and that women are at increased risk for developing depression when their partners are depressed. Dyadic psychosocial interventions that target patients and their caregivers may thus be beneficial in terms of addressing depression in this this vulnerable population.